The Future of Succession Planning in Organizations - Christy, Kathleen M.; Kowalewski, Susan (Archives of Business Research, 2023)
Succession planning is a process in an organization to determine the critical positions essential for leadership, sustainability and developing a plan of action for people to assume those roles [1]. It is important to understand an organization’s culture and philosophy regarding leadership and success when understanding succession planning. Many organizations don’t consider succession planning until someone dies, retires or leaves a position [2]. Most often the organization is then is in a crisis situation, which can lead to poor decision-making, as well as exhibiting a lack of confidence to internal and external constituents [2]. Leaders of exemplary organizations invest in knowledge of the entire organization. This paper presents concepts and recommendations related to implementing succession planning in organizations, as well as issues and roadblocks.